2015
DOI: 10.5772/60580
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Design and Analysis of Four Types of Variable Stiffness Actuators Based on Spring Pretension

Abstract: The variable stiffness actuator (VSA) is an open research field. This paper introduces the conceptual design and analysis of four types of novel variable stiffness actuators (VSAs). The main novelty of this paper is focused on the convenience control of the torque and stiffness of the actuator. We do not need to design complicated control strategies to achieve the desired actuating torque and output stiffness. This feature is beneficial for real-time control. In order to achieve this advantage, three types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Therefore, the stiffness can be properly controlled to reduce energy requirements during the execution of repetitive tasks, as explained in Reference [40]. Reviews on variable stiffness actuators can be found in References [41][42][43][44], whereas a comparison of several design of VSA based on spring pretension is illustrated in Reference [45].…”
Section: Serial Compliance Elementsmentioning
confidence: 99%
“…Therefore, the stiffness can be properly controlled to reduce energy requirements during the execution of repetitive tasks, as explained in Reference [40]. Reviews on variable stiffness actuators can be found in References [41][42][43][44], whereas a comparison of several design of VSA based on spring pretension is illustrated in Reference [45].…”
Section: Serial Compliance Elementsmentioning
confidence: 99%
“…Another study [17] reported a VSA created only from linear springs; whereas Guo et al [18] proposed four types of VSAs based on spring pretension with use of many parallel springs set at different angles. With this system, variable stiffness is achieved by adjusting the end points of the springs.…”
Section: Variable Stiffness and Impedance Actuatorsmentioning
confidence: 99%
“…Therefore, the flexible joint based on a variable stiffness actuator is considered an important strategy, becoming the focus of the relevant research. The variable stiffness actuators include linear [7][8][9] and rotational [10,11]. Linear actuators are usually applied for the knee joint, legged robotics, and finger joints.…”
Section: Introductionmentioning
confidence: 99%